Approche dynamique du déroulement d’activités humaines en mer côtière - Matthieu Le Tixerant; Françoise Gourmelon (Cybergeo)
Coastal seas are the seat of numerous human activities interacting with the natural environment. In this open space, understanding human activities progress is much more complex. The methodology aims to model human activities progress through spatio-temporal filters. This conceptual approach is preliminar to simulating human marine activities dynamics. Coupling the simulator with a GIS allows us to produce synthetic maps which provide synthetic information useful for coastal sea management. This paper focuses on the fishing activity.